The Transatlantic Alliance on the Eve of the New Millennium - Trifunovska, Snežana, (International Law - Book Archive pre-2000., 1996)
Within these pages is a veritable banquet for those who savour the politics of international security. The reader is offered factual analysis, insight, new perspectives, revisited concepts, problem spotting and recipes for solutions. Academic observers from a dozen different countries in Eastern and Western Europe and on both sides of the Atlantic subject a large number of questions of topical interest in the security field to one or other of these forms of treatment. Their debate embraces reinforcement of the European pillar of the Alliance; adjustment of the balance of responsibilities between the two sides of the Atlantic; and shoring up the transatlantic partnership and perhaps broadening it into that elusive concept, a `transatlantic community', stretching into economic and other fields. They address the perceived security vacuum in parts of Central and Eastern Europe and discuss measures to build up greater confidence between former Cold War antagonists and ways of developing in them the habits of co-operation rather than counter-operation. They draw up architectural designs for the security of the twenty-first century and grapple with the conflict of ideas circulating about the Alliance's future and particularly about its future relationship with Russia. Isolationism, nationalism, multilateralism, realism, constructivism and other -isms are helpfully put into context. Renationalisation, denationalisation and identities in formation or in decline are also investigated. See Less